Targeting Photosynthesis Under Abiotic Stress - Swami, Pooja; Munjal, Renu; Deswal, Kapil (Journal of Cereal Research, 2022)
Earth sustains life due to the presence of the photosynthesis process that produced food for other organisms on our planet. But rapidly changing climate of most of the continents results in losses to photosynthetic machinery that ultimately lead to threatening food security worldwide. The major limiting factor in plant growth is abiotic stresses which are thought to become more severe in near future also unabated increase in the world population the future potential yield of commercial crops is under serious threat. The global food demand is expected to double in the coming years. The reduction of photosynthetic capability of various crops due to various abiotic stresses factors like heat, salinity, drought, high light, and heavy metal are gathered to understand the mechanism of stress tolerance and wider adaptability of different crops. We highlight the impact of various abiotic stresses on the performance of the photosynthetic process in crop plants. Further, we reviewed the different new generation solutions for photosynthesis improvements include improving enzyme (Rubisco) kinetic properties, C4 pathway into C3 crops, reduce photorespiration, canopy architecture, light capture, and photosynthetic models approaches also we have reviewed the role of genetic engineering crops with improved photosynthesis process that withstand and provide significant yields under environmental stresses. A better understanding of the photosynthetic process under stress conditions could support the development of new crops with higher yield even under adverse environments.